Pendampingan Program Anti Bullying Menuju Sekolah Ramah Anak Di Madrasah Ibtidaiyah Se Kecamatan Menganti - Fauziah, Ria Resti (LP3M IAIFA Kediri, 2024)
The anti-bullying mentoring program at Madrasah Ibtidaiyah in Menganti District aims to create a school environment that is child-friendly and free from bullying. This program involves various parties, including teachers, students, parents and the local community, in order to increase awareness and understanding of the negative impacts of bullying. Through a series of activities such as seminars, workshops and anti-bullying campaigns, this program has succeeded in creating positive behavioral changes in students, the formation of new institutions in the form of bullying handling teams, and the emergence of local leaders among students. The research results show that this mentoring program is effective in reducing cases of bullying and increasing awareness of the importance of a safe and comfortable school environment, as well as bringing about the desired social transformation.